1987
DOI: 10.1172/jci113025
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an abnormal species of apolipoprotein B, apolipoprotein B-37, associated with familial hypobetalipoproteinemia.

Abstract: Steinberg and colleagues have previously described a unique kindred with normotriglyceridemic hypobetalipoproteinemia (1979. J. Clin. Invest. 64:292-301). In a reexamination of this kindred, we found an abnormal apolipoprotein (apo) B species, apo B-37 (203,000 mol wt), in the plasma lipoproteins of multiple members of the kindred. In affected individuals apo B-37 was found in very low density lipoproteins, along with the normal apo B species, apo B-100 and apo B-48. High density lipoproteins (HDL) also contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(65 citation statements)
references
References 38 publications
(35 reference statements)
3
62
0
Order By: Relevance
“…Apo B-40 was the only detectable apo B species in the d>1.124 g/ml fraction. In this regard, the apo B-40 is similar to the apo B-37 species reported by Young et al 7 in that it is found in particles with HDL density; however, it should be noted that apo B-40 is found in much lower concentrations in plasma and HDL than apo B-37. Also, there was no evidence of a "peak" of apo B-40 in the HDL density range as was reported for apo B-37 by Young et al…”
Section: Characterization Of Upoprotelnssupporting
confidence: 82%
“…Apo B-40 was the only detectable apo B species in the d>1.124 g/ml fraction. In this regard, the apo B-40 is similar to the apo B-37 species reported by Young et al 7 in that it is found in particles with HDL density; however, it should be noted that apo B-40 is found in much lower concentrations in plasma and HDL than apo B-37. Also, there was no evidence of a "peak" of apo B-40 in the HDL density range as was reported for apo B-37 by Young et al…”
Section: Characterization Of Upoprotelnssupporting
confidence: 82%
“…Coomassie blue staining documented the presence of intact apolipoprotein B and of fragments resembling those seen after oxidative modification in vitro (6). That these lower molecular weight fragments were, indeed, derived from apolipoprotein B was confirmed by Western blot techniques, using a panel of apolipoprotein-B-specific mAbs (10). For example, both the intact apolipoprotein B-100 and a number of lower molecular weight fragments reacted with mAb MB-47 (Fig.…”
Section: Methodsmentioning
confidence: 76%
“…This finding is in agreement with our observation that apoB-38.7 was not present in the dϾ1.21 g/mL fraction. ApoB-37, 5 apoB-38.9, 17 apoB-40, 34 and apoB-46 35 were reported to be present in HDL, but apoB-39, 12 apoB-50, 21 and the other species larger than apoB-50 were not, indicating that a portion of the apoB between apoB-37 and apoB-46 is essential for distribution in HDL. This finding is consistent with our observation that apoB-38.7 was distributed in HDL.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that the buoyant density of the apoB-containing lipoproteins is largely proportional to the size of apoB between apoB-31 and apoB-37. It has been reported that apoB-31, 31 apoB-32, 32 and apoB-32.5 33 are present in the dϾ1.21 g/mL fraction, but apoB-37 is not, 5 suggesting that a portion of the apoB proteins between apoB-32.5 and apoB-37 is critical for the distribution to the dϾ1.21 g/mL fraction. This finding is in agreement with our observation that apoB-38.7 was not present in the dϾ1.21 g/mL fraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation